Analisis Informasi Anatomi pada Pemeriksaan CT Scan Ankle Joint Menggunakan Protokol CT Abdomen Dan Protokol CT Ankle Joint di Instalasi Radiologi Rumah Sakit Gading Pluit Jakarta - Gunawan Khairul Anam; Bagus Abimanyu; Edy Susanto (Jurnal Imejing Diagnostik (JImeD), 2015)
Backgroud: In Radiology Installation of Gading Pluit Jakarta Hospital, CT Scan of the ankle joint uses abdomen CT protocol because it produces image quality that is considered to be able to diagnose and provide adequate information, although in Gading Pluit Jakarta Hospital there is a choice of CT protocol with Ultra High Resolution (UHR). The purpose of this study was to determine the difference of anatomical information on ankle joint CT scan between abdomen CT protocol and ankle joint CT protocol at Gading Pluit Jakarta Hospital and which protocol is better between UHR ankle protocol and abdomen protocol.Methods: This type of this research was an experimental study. The study was conducted by performing two times of scanning with different protocols such as abdomen protocol and ankle joint protocol on ankle joint CT scan examination. The image was assessed by seven radiology physicians by viewing the information of the image. Data were analyzed statistically with Wilcoxon test.Results: The results of this study showed that there was significant difference between abdomen protocol and UHR ankle joint protocol, with Wilcoxon p.value = 0,00 (p 0,05) and on ankle joint CT Scan examination, UHR ankle joint protocol was better than abdomen protocol so that the UHR ankle protocol was well applied in daily examination on CT scan of ankle joint.Conclusion: There was difference between the abdomen CT protocol and ankle joint CT protocol (UHR) in Radiology Installation of Gading Pluit Jakarta Hospital. The ankle CT protocol (UHR) was better than the abdomen CT protocol on ankle joint CT scan examination in Radiology Installation of Gading Pluit Jakarta Hospital.